2018
DOI: 10.1017/s0950268818001243
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating vaccination strategies to control foot-and-mouth disease: a country comparison study

Abstract: Vaccination is increasingly being recognised as a potential tool to supplement 'stamping out' for controlling foot-and-mouth disease (FMD) outbreaks in non-endemic countries. Infectious disease simulation models provide the opportunity to determine how vaccination might be used in the face of an FMD outbreak. Previously, consistent relative benefits of specific vaccination strategies across different FMD simulation modelling platforms have been demonstrated, using a UK FMD outbreak scenario. We extended this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Specifically, as seen within the past decade in South Korea, a strict approach of stamping out to maintain freedom from FMD without vaccination may not be feasible when the disease pressure is overwhelming [6,[154][155][156][157][158]. Additionally, when indirect costs associated with FMD outbreaks, such as job losses within the livestock sector, and losses associated with reduced tourism are accounted for, the estimated financial benefits of vaccination often increase [159][160][161].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, as seen within the past decade in South Korea, a strict approach of stamping out to maintain freedom from FMD without vaccination may not be feasible when the disease pressure is overwhelming [6,[154][155][156][157][158]. Additionally, when indirect costs associated with FMD outbreaks, such as job losses within the livestock sector, and losses associated with reduced tourism are accounted for, the estimated financial benefits of vaccination often increase [159][160][161].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination may help suppress the spread of infection (Pluimers et al, 2002) and reduce the need for large-scale culling of at-risk animals (Paton et al, 2006). Epidemiological models can help inform when/where/how suppressive vaccination might best be deployed (Bates et al, 2003; Tildesley et al, 2006; Backer et al, 2012a; Tildesley et al, 2012; Boklund et al, 2013; Porphyre et al, 2013; Hayama et al, 2013; Durr et al, 2014; Rawdon et al, 2018; Marschik et al, 2020), and how constraints on vaccine supply and/or response personnel might impact the effectiveness of control (Abdalla et al, 2005; Roche et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This may include whether vaccination should be adopted as an additional response measure. Various studies have indicated that emergency vaccination, if implemented early for large FMD outbreaks, benefits earlier control (Rawdon et al, 2018;Roche et al, 2015;Sanson et al, 2014Sanson et al, , 2017. Vaccination, however, showed minimal effect during small outbreaks (Dürr et al, 2014) and could result in unnecessary competition for resources which are already strained.…”
Section: Introductionmentioning
confidence: 99%